Effectiveness Of Online Service System In The Office Of National Land Agency Of Semarang City - Delvi Amalia Rosa; Widya Pratiwi Asmara; Aryani Witasari (Jurnal Akta, 2019)
The research of "Effectiveness of Online Service System at Land Office of Semarang" aims to determine how the effectiveness of online services in the Land Office of Semarang, determine the impact and solutions online services in the Office of the National Land Agency of Semarang.The method used in this paper is the specification method of sociological judicial collecting data to obtain data that will be used as the contents of a journal through interviews with officials of the National Land Agency of Semarang or by observing the object to obtain data. Then it will be carried out analysis of data obtained from various sources.The results showed that the use of systems-based services online have efficacy and good effect because it allows officers to check the lack of service the Land Office of Semarang, while the various obstacles that arise regarding the use of services of National Land Agency online, but all obstacles superbly gain solution. Both solutions have been realized and those still in the proposal.Keywords: Effectiveness; Service; National Land Agency